2009
DOI: 10.1016/j.tripleo.2009.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ramus, condyle, masseter muscle, and occlusal force before and after sagittal split ramus osteotomy in patients with mandibular prognathism

Abstract: Assessment of ramus, condyle, masseter muscle, and occlusal force before and after sagittal split ramus osteotomy in patients with mandibular prognathism 2 Assessment of ramus, condyle, masseter muscle, and occlusal force before and after sagittal split ramus osteotomy in patients with mandibular prognathism Abstract Purpose: The purpose of this study was to examine the relationship between the morphologies of the masseter muscle and the ramus and occlusal force before and after sagittal split ramus osteotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…The results by RBSM using frontal cephalogram suggest that the difference between the right and left sides could also be improved after surgery in the symmetry and asymmetry groups, though not completely in the asymmetry group (Ueki et al, 2009a(Ueki et al, , 2009b(Ueki et al, , 2010.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The results by RBSM using frontal cephalogram suggest that the difference between the right and left sides could also be improved after surgery in the symmetry and asymmetry groups, though not completely in the asymmetry group (Ueki et al, 2009a(Ueki et al, , 2009b(Ueki et al, , 2010.…”
Section: Discussionmentioning
confidence: 94%
“…The incidence of internal derangement in asymmetrical prognathia patients is higher than in symmetrical mandibular prognathia, and this finding is associated with a difference in TMJ morphology of both sides (Ueki et al, 2000). Furthermore, a previous study suggested that the masseter muscle area did not significantly differ from the preoperative status 1 year after SSRO, although postoperatively 1 year ramus width, ramus area and condylar area were significantly larger than the preoperative values (Ueki et al, 2009a(Ueki et al, , 2009b. However, there is no study on change in condylar bone quality following SSRO.…”
Section: Introductionmentioning
confidence: 89%
“…30 Ueki et al found no changes in cross-sectional area and direction of the MAS muscles in 26 patients, who had undergone a BSSO setback. 31 Their measurements were made 1 year after surgery. To the best of the authors' knowledge, no similar studies have been carried out on patients undergoing an advancement BSSO to treat mandibular hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…As deformidades dentofaciais são caracterizadas por más oclusões acentuadas tanto esqueletais quanto dentoalveolares (TUCKER, 2000), acompanhadas de alterações nas funções orofaciais, verificadas principalmente na mastigação (BERRETIN-FELIX; JORGE; GENARO, 2010;BIANCHINI, 1999;BIANCHINI, 2011;TRAWITZKI, 2004;TRAWITZKI, 2009), na força de mordida (SILVA, 2014;THROCKMORTON, 2006;TRAWITZKI et al, 2011;ZARRINKELK et al, 1996), na eficiência mastigatória (PICINATO-PIROLA, 2010;PICINATO-PIROLA et al, 2012;THROCKMORTON, 2006), assim como na atividade eletromiográfica (GADOTTI; BERZIN; BIASOTTO-GONZALEZ, 2005;MORENO et al, 2008;FARIAS et al, 2013;TRAWITZKI et al, 2006;TRAWITZKI et al, 2010;ZARRINKELK et al, 1996) e na morfologia dos músculos mastigatórios (KATSUMATA et al, 2004;UEKI et al, 2009;TRAWITZKI et al, 2006a).…”
Section: Introductionunclassified